Hipk2 cooperates with p53 to suppress γ-ray radiation-induced mouse thymic lymphoma - Mao, J-H; Wu, D; Kim, I-J; Kang, H C; Wei, G; Climent, J; Kumar, A; Pelorosso, F G; DelRosario, R; Huang, E J; Balmain, A (Oncogene, 2012)
A genome-wide screen for genetic alterations in radiation-induced thymic lymphomas generated from p53 +/− and p53 −/− mice showed frequent loss of heterozygosity (LOH) on chromosome 6. Fine mapping of these LOH regions revealed three non-overlapping regions, one of which was refined to a 0.2 Mb interval that contained only the gene encoding homeobox-interacting protein kinase 2 ( Hipk2 ). More than 30% of radiation-induced tumors from both p53 +/− and p53 −/− mice showed heterozygous loss of one Hipk2 allele. Mice carrying a single inactive allele of Hipk2 in the germline were susceptible to induction of tumors by γ-radiation, but most tumors retained and expressed the wild-type allele, suggesting that Hipk2 is a haploinsufficient tumor suppressor gene for mouse lymphoma development. Heterozygous loss of both Hipk2 and p53 confers strong sensitization to radiation-induced lymphoma. We conclude that Hipk2 is a haploinsufficient lymphoma suppressor gene.